Health Inequalities among People Experiencing Food Insecurity. An Intersectional Approach - Nick Drydakis (Institute of Labor Economics (IZA), 2023)
The study examines the socio-economic determinants of physical health among populations experiencing food insecurity and receiving free meals in soup kitchens in the Prefecture of Attica, Greece. Data were collected from the same six soup kitchens in 2012, 2017, and 2021, resulting in a dataset of 1,533 observations. The study revealed that periods characterised by an economic recession are associated with deteriorated physical health of food-insecure people. Moreover, the study found that physical health deteriorations among food-insecure people are associated with older age, female gender, immigration status, disability and/or long-term health conditions, LGBT status, unemployment, economic inactivity, homelessness, living below the poverty threshold, long-term food dependency, illicit drug consumption, and residing in low- and middle-class areas. The study proposes the Intersectional Model of Health Inequalities, which integrates multiple factors involved in shaping the health inequalities of people experiencing food insecurity, from macro-level factors such as a country's economic performance to individual-level factors like education, employment status and demographic characteristics. The model emphasizes that low-income populations should not be treated as a homogeneous entity. Its goal is to inform policymakers about the diverse health inequalities experienced by people with low incomes.
Keywords: I32; I10; I14; 330; food insecurity; poverty; health